Epilepsy Metaphors : Liminal Spaces of Individuation in American Literature 1990-2015. - Vaja, Eleana (Lettre., 2017)
Between 1990 and 2015, American literature saw the emergence of a new corpus of epilepsy metaphors which tackle the stigma of epilepsy within three areas: society, body, and language. Eleana Vaja introduces concepts such as protometaphors, relational meta.